Hannah Arendt, leitora de Montesquieu: ensaio sobre o totalitarismo e as revoluções - Vinícius Batelli de Souza Balestra (2016)
Hannah Arendt places Montesquieu as an author sui generis within the tradition of political thought. While the so called Great Tradition assumes preconceived political models to think about politics, Montesquieu would be an example of a thinker that really used the human experience to form his political theory. In the work of Hannah Arendt, Montesquieu appears in two fundamental moments: to feature totalitarianism as a form of government; and to analyze the American Revolution from a plural and decentralized concept of power. This work aims to analyze these two moments of the arendtian reading of Montesquieu.